An affordable and reliable assessment of aquatic decomposition: Tailoring the Tea Bag Index to surface waters - Seelen, Laura M S; Flaim, Giovanna; Keuskamp, Joost; Teurlincx, Sven; Arias Font, Raquel; Tolunay, Duygu; Fránková, Markéta; Šumberová, Kateřina; Temponeras, Maria; Lenhardt, Mirjana; Jennings, Eleanor; de Senerpont Domis, Lisette N (Water research, 2019)
Litter decomposition is a vital part of the global carbon cycle as it determines not only the amount of carbon to be sequestered, but also how fast carbon re-enters the cycle. Freshwater systems play an active role in the carbon cycle as it receives, and decomposes, terrestrial litter material alongside decomposing aquatic plant litter. Decomposition of organic matter in the aquatic environment is directly controlled by water temperature and nutrient availability, which are continuously affected by global change. We adapted the Tea Bag Index (TBI), a highly standardized methodology for determining soil decomposition, for lakes by incorporating a leaching factor. By placing Lipton pyramid tea bags in the aquatic environment for 3 h, we quantified the period of intense leaching which usually takes place prior to litter (tea) decomposition. Standard TBI methodology was followed after this step to determine how fast decomposition takes place (decomposition rate, k1) and how much of the material cannot be broken down and is thus sequestered (stabilization factor, S). A Citizen Science project was organized to test the aquatic TBI in 40 European lakes located in four climate zones, ranging from oligotrophic to hypereutrophic systems. We expected that warmer and/or eutrophic lakes would have a higher decomposition rate and a more efficient microbial community resulting in less tea material to be sequestered. The overall high decomposition rates (k1) found confirm the active role lakes play in the global carbon cycle. Across climate regions the lakes in the warmer temperate zone displayed a higher decomposition rate (k1) compared to the colder lakes in the continental and polar zones. Across trophic states, decomposition rates were higher in eutrophic lakes compared to oligotrophic lakes. Additionally, the eutrophic lakes showed a higher stabilization (S), thus a less efficient microbial community, compared to the oligotrophic lakes, although the variation within this group was high. Our results clearly show that the TBI can be used to adequately assess the decomposition process in aquatic systems. Using "alien standard litter" such as tea provides a powerful way to compare decomposition across climates, trophic states and ecosystems. By providing standardized protocols, a website, as well as face to face meetings, we also showed that collecting scientifically relevant data can go hand in hand with increasing scientific and environmental literacy in participants. Gathering process-based information about lake ecosystems gives managers the best tools to anticipate and react to future global change. Furthermore, combining this process-based information with citizen science, thus outreach, is in complete agreement with the Water Framework Directive goals as set in 2010.
Keywords: jezera; čaj; podnebí; Carbon; Tea; uhlík; Lakes; Climate; ekosystém; Ecosystem